Constructing media reality with an agenda in mind - О. N. Goryacheva (Вестник университета)
In the world of virtual reality, it becomes quite difficult for the recipient of information to understand how much the image he uses, created in media reality, corresponds to the phenomenon of social reality, of which it is a reflection. The construction of media reality in the media is of particular interest for research in the field of sociology, cultural studies, psychology, linguistics, advertising, PR. The study of the genesis of media reality in the paradigm of mass media is the basis for identifying the main trends in the development of communication science. Of interest is the interdependence of the agenda and the means of influencing consumers of information used in the media. The relevance of the work is associated with the understanding that the construction of media reality turns into a media process. The allocation of priority information in the media stream becomes problematic: the consciousness of the recipient is significantly overloaded the individual does not have time to analyze the information received, but only gives him a superficial emotional assessment. The article analyses mass media materials that reflect the agenda and affect the construction of media reality. The practical significance of the study of the potential of mass media in the construction of media reality is to identify priority topics for the agenda of publications that affect the consumer of information content.